Fabrication and Characterization of GaAsP Nanowire-on-Silicon Tandem Photovoltaic Cells - Wood, Brendan (My University, 2017)
One-dimensional vertical nanostructures, nanowire arrays, are investigated for applications in photovoltaics. Specifically, III-V core-shell p-i-n nanowire arrays are grown by molecular beam epitaxy on silicon substrates, using the self-assisted vapour-liquid-solid growth method. GaAs1-xPx nanowires are grown with an optimized composition to maximize the potential efficiency of a GaAsP nanowire-on-silicon tandem solar cell under AM1.5G illumination. Photovoltaic devices are fabricated and assessed by optical and electrical characterization techniques, to identify areas for refinement of device design and processing. Combining the unique properties of nanowire arrays, the quality and tunability of III-V materials, and the economics and infrastructure of silicon-based device fabrication, this work examines a novel approach to affordable renewable energy. Methods of substrate removal via etching are investigated for optical characterization of nanowire arrays, and an improved technique for electrical characterization of ITO contacts is explored. The first nanowire-on-silicon tandem device utilizing a radial p-n junction nanowire structure is reported, achieving an open circuit voltage of 1.2 V, a short circuit current density of 7.6 mA/cm2, a fill factor of 40%, and an efficiency of 3.5%. Finally, projects for future improvements to the work described herein are suggested.
Keywords: III-V; nanowire; photovoltaics; tandem cell